TELAAH HISTORIS TERHADAP TEORI EVOLUSI CHARLES DARWIN DITINJAU DARI REVOLUSI SAINS THOMAS S. KUHN - Galuh Nur Fattah; Gede Agus Siswadi (Institut Filsafat dan Teknologi Kreatif Ledalero, 2022)
Abstract: This article specifically describes how a scientific theory is formed and placed as an epistemic truth, even in the end it becomes a paradigm that influences scientific methodologies in various different scientific fields. This is in line with the scientific revolution proposed by Thomas S. Kuhn. The discussion in this article will focus on the development of the theory of evolution proposed by Charles Darwin in the field of biology, viewed from the perspective of the scientific revolution of Thomas S. Kuhn. This effort was made because in its development, Darwin's theory of evolution has historically been the starting point for theoretical revolutions in the field of biology, and even in other scientific fields. This historical explanation of how the development process of Darwin's theory of evolution shifted, and even undermined previous scientific theories, became a starting point for a radical theoretical transformation in the development of science which was viewed from Kuhn's analysis through his theoretical schema of the revolution of a scientific theory. This becomes very important for researchers and the general public, especially to provide an explanation that the epistemic truth in science is not a sudden speculative knowledge, as is the ontological truth in religious knowledge and cultural knowledge. The methodical approach used in this article will use a historical continuity approach, heuristics, and interpretation. The type of analysis in this article falls into the analysis of scientific theory. This article was written with the aim of providing a description, evidence, and argument that the paradigm shift of science from the pre-Darwinian evolutionary period to the Darwinian evolutionary period is a description of a radical theoretical transformation process that occurs instantly in a scientific field, which in Kuhn's thinking is passed through The main phases are normal science, anomaly, crisis, and scientific revolution.Keywords: The Theory of Evolution, Scientific Revolution, Charles Darwin, Thomas S. Kuhn, Epistemic Truth